2015
DOI: 10.1007/s13280-015-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

A method to estimate the impact of clear-cutting on nutrient concentrations in boreal headwater streams

Abstract: Large-scale forestry operations, like clearcutting, may impair surface water quality if not done with environmental considerations in mind. Catchment and country level estimates of nutrient loads from forestry are generally based on specific export values, i.e., changes in annual exports due to the implemented forestry operations expressed in kg ha -1 . We introduce here a specific concentration approach as a method to estimate the impact of clear-cutting on nutrient concentrations and export in headwater stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Second, the proportion of clear-cuts in our catchments (18-44%) was just around the threshold level (~30%) above which significant effects on hydrology and water chemistry can be expected in our 15 study region (Schelker et al 2013;Ide et al 2013;Palviainen et al 2014;Schelker et al 2014). These threshold values can vary and are highly site-specific (Kreutzweiser et al 2008;Palviainen et al 2015). For example, the relatively high baseline DOC concentrations in our streams and lakes (20 and 29 mg L -1 , respectively) are potentially less likely to be further enhanced by forest clear-cuts.…”
mentioning
confidence: 74%
“…Second, the proportion of clear-cuts in our catchments (18-44%) was just around the threshold level (~30%) above which significant effects on hydrology and water chemistry can be expected in our 15 study region (Schelker et al 2013;Ide et al 2013;Palviainen et al 2014;Schelker et al 2014). These threshold values can vary and are highly site-specific (Kreutzweiser et al 2008;Palviainen et al 2015). For example, the relatively high baseline DOC concentrations in our streams and lakes (20 and 29 mg L -1 , respectively) are potentially less likely to be further enhanced by forest clear-cuts.…”
mentioning
confidence: 74%
“…Different studies have confirmed that young forests are usually not able to limit nitrogen losses in the years following a clear cut (e.g. Palviainen et al 2015;Vitousek and Melillo 1979) and we checked with TNT2 that it simulated higher leaching on woodlots than on extensive grasslands when implanted on previous croplands (data not presented).…”
Section: Landscape Management Scenariosmentioning
confidence: 91%
“…Deforestation often results in the degradation of water quality which includes an increase in temperature, sedimentation, and nutrient enrichment [5][6][7][8][9]. In Malaysia, soil loss from logging activities had been predicted to highlight the potential risk posed by logging within water catchment areas [10].…”
Section: Introductionmentioning
confidence: 99%